INNOVATIVE APPROACH TO THE DEVELOPMENT OF ELECTRICAL INSTALLATION EQUIPMENT - Maxmudov Yunusxon Xusanboy o’g’li (Research Focus International Scientific Journal, 2022)
Any object of the modern world needs electricity, which means that it needs reliable and modern electrical work. Construction and installation works are carried out during the construction of new facilities, during the reconstruction or replacement of existing electrical equipment and electrical networks.